2021
DOI: 10.1089/aut.2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Behavioral Intervention for Driving for Autistic Teens and Adults: A Pilot Study

Abstract: Background: For many autistic individuals approaching adulthood, interventions to promote skills toward independence are lacking. Driving is an important ability to cultivate as it may be a critical step to attaining independence, securing and maintaining work, and fostering relationships. Only about one third of able autistic individuals drive independently, and fear to drive is a common reason for not driving. Methods: This initial pilot study was a 3-month open trial to investigate the feasibility, acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Overall, these elevations begin to contribute to the relationship of emotion dysregulation and negative affect and perceived DD in new autistic drivers. These findings also align with the idea that autistic individuals may need specific support for socio-emotional differences when learning to drive as, for example, the intervention recently described in Baker-Ericzén et al (2020). In addition, virtual reality driving simulations can transform generalized skill instruction for autistic learners, highlighted as a unique learning difficulty by Klin et al (2003), by providing adaptive driving instructions that can respond to their real-time physiological arousal (Bian et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Overall, these elevations begin to contribute to the relationship of emotion dysregulation and negative affect and perceived DD in new autistic drivers. These findings also align with the idea that autistic individuals may need specific support for socio-emotional differences when learning to drive as, for example, the intervention recently described in Baker-Ericzén et al (2020). In addition, virtual reality driving simulations can transform generalized skill instruction for autistic learners, highlighted as a unique learning difficulty by Klin et al (2003), by providing adaptive driving instructions that can respond to their real-time physiological arousal (Bian et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Two studies utilized VR driving simulators to train driving skills and executive functioning for adults with ASD ( 18 , 21 ). Lastly, a study reported on the use of a VR application installed onto tablets to train community living skills such as shopping at a supermarket and preparing a suitcase ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies targeted the functional skills of driving in adults with ASD using VR driving simulators. The Cognitive Behavioral Intervention for Driving (CBID) consisted of cognitive behavioral strategies to enhance executive functions and generalizing them to driving ( 18 ). Intervention was carried out weekly over 10 sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Fornasari et al trained individuals with ASD in urban virtual environments to navigate and explore the area [21]; Dixon et al taught children with ASD how to recognize safe road-crossing conditions in an immersive VR environment [19]. In addition to street-crossing skills, driving skills are also needed to foster individual independence, and 45% (n = 9) of studies focused on training driving skills for people with ASD [22][23][24][25][26][27][28][29][30], e.g., embedding an adaptive model within a driving simulator in VR, adjusting the task difficulty through the acquisition and analysis of multimodal data from the user's driving task, and the personalization of the driving task to achieve the optimal…”
Section: Intervention Purposementioning
confidence: 99%
“…Fornasari et al trained individuals with ASD in urban virtual environments to navigate and explore the area [21]; Dixon et al taught children with ASD how to recognize safe road-crossing conditions in an immersive VR environment [19]. In addition to street-crossing skills, driving skills are also needed to foster individual independence, and 45% (n = 9) of studies focused on training driving skills for people with ASD [22][23][24][25][26][27][28][29][30], e.g., embedding an adaptive model within a driving simulator in VR, adjusting the task difficulty through the acquisition and analysis of multimodal data from the user's driving task, and the personalization of the driving task to achieve the optimal training effect [23,24]; helping ASD individuals to reduce their fear of driving and improve their driving cognition and performance [29]. Meanwhile, 10% (n = 2) of the studies focused on training ASDs in air travel skills [31,32], e.g., Miller et al conducted a training program for ASD patients using an iPhone X and Google Cardboard device that lasted 3 consecutive weeks, followed by a real air travel rehearsal at San Diego International Airport in the fourth week [32].…”
Section: Intervention Purposementioning
confidence: 99%